Parenchymal cues define Vegfa-driven venous angiogenesis by activating a sprouting competent venous endothelial subtype - Préau, Laetitia; Lischke, Anna; Merkel, Melanie; Oegel, Neslihan; Weissenbruch, Maria; Michael, Andria; Park, Hongryeol; Gradl, Dietmar; Kupatt, Christian; Le Noble, Ferdinand (Nature Communications, 2024)
Formation of organo-typical vascular networks requires cross-talk between differentiating parenchymal cells and developing blood vessels. Here we identify a Vegfa driven venous sprouting process involving parenchymal to vein cross-talk regulating venous endothelial Vegfa signaling strength and subsequent formation of a specialized angiogenic cell, prefabricated with an intact lumen and pericyte coverage, termed L-Tip cell. L-Tip cell selection in the venous domain requires genetic interaction between vascular Aplnra and Kdrl in a subset of venous endothelial cells and exposure to parenchymal derived Vegfa and Apelin. Parenchymal Esm1 controls the spatial positioning of venous sprouting by fine-tuning local Vegfa availability. These findings may provide a conceptual framework for understanding how Vegfa generates organo-typical vascular networks based on the selection of competent endothelial cells, induced via spatio-temporal control of endothelial Kdrl signaling strength involving multiple parenchymal derived cues generated in a tissue dependent metabolic context.